The effect of copper sulphate on froth stability - Nyabeze, Wadzanai (Department of Chemical Engineering, 2016)
Froth flotation is a mineral beneficiation process implemented in the recovery of valuable minerals from unwanted gangue material. Copper sulphate is used as an activator in the flotation of base metal sulphides (BMS) as it promotes interaction of collector molecules with the mineral surfaces. It is also used in certain platinum group minerals (PGM) flotation operations in South Africa although the mechanism by which improvements in flotation performance are achieved is not well understood. Some investigations suggest that changes in flotation performance are affected by changes in the froth phase, rather than activation of minerals by true flotation in the pulp zone. The present study focussed on exploring the effect of using copper sulphate as an activator and sodium isobutyl xanthate (SIBX) as a collector on froth stability in Platinum Group Mineral (PGM) operations. This was done on two PGM containing ores namely Merensky and UG2 (Upper Group 2) ores from the Bushveld Complex of South Africa. The dynamic froth stability factor (Σ) and froth half life time (t1/2) were used as measures of froth stability. These were obtained using a froth stability column which is a non-overflowing system. The effect of activation on pure minerals in the pulp phase was also analysed using a microflotation cell which eliminates the froth phase and hydrodynamic interactions found in normal flotation cells. The microflotation cell was used as a measure of hydrophobicity which was directly linked to the flotation recovery. The adsorption of reagents onto the mineral surfaces was confirmed by the use of zeta potential and ethylenediaminetetraacetic acid (EDTA) extraction of surface products. The pulp phase effects were analysed through the floatability of pure minerals and analysis of surface products after copper sulphate activation and these were linked to the outcomes from the froth stability tests. It was hypothesised that copper sulphate destabilised the froth for a Merensky ore and for a UG2 ore but due to different reasons because of the mineralogical compositions of the two ores. For the Merensky ore, the froth destabilisation was postulated to be due to the formation of Cu(I) on the base metal sulphide surfaces which promotes the formation of hydrophobic copper-xanthate species. This would result in an increase in contact angle which promotes bubble coalescence. For the UG2 ore which has far less base metal sulphides than Merensky ore, it was hypothesised that the destabilisation of the froth would be due to the non-selective precipitation of hydrophilic colloidal hydroxides on mineral surfaces which reduce the amount of hydrophobic froth stabilising particles reporting to the froth phase.